Williams obstetrics - Cunningham, F. Gary (New York : McGraw Hill, 2022)
"This landmark text begins with fundamental discussions of reproductive anatomy and physiology. These dovetail into clinical chapters covering obstetrical complications such as preterm labor, pregnancy-related infection, hemorrhage, and hypertension, among others. Representing the culmination of a century of clinical thought, the new twenty-sixth edition is enhanced by more than 1,000 full-color illustrations plus an increased emphasis on the fast-growing subspecialty of maternal-fetal medicine"--
Includes bibliographical references and index.
Keywords: Obstetrics -- methods